Self-Reported Prevalence of Symptomatic Adverse Reactions to Gluten and Adherence to Gluten-Free Diet in an Adult Mexican Population - Ontiveros, Noe (Nutrients, 2015)
The prevalence of symptomatic adverse reactions to gluten and adherence to gluten-free diet in Latin American countries is unknown. These measurements are strongly linked to gluten-related disorders. This work aimed to estimate the prevalence of adverse reactions to oral gluten and the adherence to gluten-free diet in the adult Mexican population. To reach this aim, a self-administered questionnaire was designed and tested for clarity/comprehension and reproducibility. Then, a self-administered questionnaire-based cross-sectional study was conducted in the Mexican population. The estimated prevalence rates were (95% CI): 11.9% (9.9–13.5) and 7.8 (6.4–9.4) for adverse and recurrent adverse reactions to gluten respectively; adherence to gluten-free diet 3.7% (2.7–4.8), wheat allergy 0.72% (0.38–1.37); celiac disease 0.08% (0.01–0.45), and NCGS 0.97% (0.55–1.68). Estimated pooled prevalence of self-reported physician-diagnosis of gluten-related disorders was 0.88% (0.49–1.5), and 93.3% respondents reported adherence to gluten-free diet without a physician-diagnosis of gluten-related disorders. Symptom comparisons between those who reported recurrent adverse reactions to gluten and other foods showed statistically significant differences for bloating, constipation, and tiredness (p < 0.05). Gluten-related disorders may be underdiagnosed in the Mexican population and most people adhering to a gluten-free diet are doing it without proper diagnostic work-up of these disorders, and probably without medical/dietician advice.